GASDYNAMIC ACTION ON THE AIR STREAM IN THE LATTICE AERODYNAMIC PROFILE - Ластівка, І. (Science-based technologies, 2011)
The summary results of further research of gas-dynamic flow control near airflow airfoils lattice of turbine en-gine are given in the article. The analysis of results of gas-dynamic flow control on parameters of aerodynamicedges traces for the components of the stator are presented. Influence describe in decreasing circular inequalityflow on inlet of compressor.